Nursing care and historical evolution: an integrative review - Camila Neumaier Alves; Ana Cândida Lopes Corrêa; Marilu Correa Soares; Sonia Maria Könzgen Meincke (Universidad de Alicante, 2015)
The aim is to identify the publications available in the literature about the history of nursing in the field of care provided by nurses. The method used included the integrative literature review, which is one of evidence-based practice resources. The search was conducted in August 2014, in the Virtual Library of Health. Were included articles that presented in titles or abstracts references to the history of nursing or the nursing care. Were excluded articles unrelated to the subject studied. For identification of the results it was decided to make a descriptive analysis of the publications and grouping of topics. It was found that the productions focus their writings on the contributions of Florence, religion and other for nursing. Moreover, prevailed discussions about the evolution of nursing through the ages and the history of care. It is understood that these findings are fundamental to locate the nurse in its history, since the nursing remains in progress and we are all actors in this art.